2013
DOI: 10.1371/journal.pone.0081041
|View full text |Cite
|
Sign up to set email alerts
|

Reaching the Unreachable: Providing STI Control Services to Female Sex Workers via Mobile Team Outreach

Abstract: BackgroundAs part of a community-randomized trial of a multicomponent intervention to prevent sexually transmitted infections, we created Mobile Teams (MTs) in ten intervention cities across Peru to improve outreach to female sex workers (FSW) for strengthened STI prevention services. MethodsThroughout 20 two-month cycles, MTs provided counseling; condoms; screening and specific treatment for Neisseria gonorrhoeae (NG), Chlamydia trachomatis (CT), and vaginal Trichomonas vaginalis (TV) infections; and periodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…Alternatively, the observed proportion of positive HIV tests may have been low since we only assessed test results from FSW attending LPHD. FSW who do not have any access to health care may have a higher HIV prevalence as suggested by findings in Peru [23]. In the Netherlands, Verscheijden et al observed a lower STI prevalence during outreach activities than at STI clinics, but this may explained by the fact that outreach activities mainly targeted FSW working in legal establishments [19, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the observed proportion of positive HIV tests may have been low since we only assessed test results from FSW attending LPHD. FSW who do not have any access to health care may have a higher HIV prevalence as suggested by findings in Peru [23]. In the Netherlands, Verscheijden et al observed a lower STI prevalence during outreach activities than at STI clinics, but this may explained by the fact that outreach activities mainly targeted FSW working in legal establishments [19, 23].…”
Section: Discussionmentioning
confidence: 99%
“…40 In Peru, a community-based intervention providing mobile services found that such services increased condom use and reduced sexually transmitted infection prevalence, including among sex workers typically not reached by government-operated services. 41 Other innovative models include health care services run by and for sex workers, such as at St. James Infirmary in San Francisco, California. 42 The St. James Infirmary model of care has been highly successful in providing confidential and nonjudgmental sexual health services for sex workers.…”
Section: Discussionmentioning
confidence: 99%
“…Outcome surveys were performed at the city-level and enrolled FSW separately from the intervention, thus one quarter of the women completing outcome surveys in the intervention cities had not participated in the intervention. Furthermore, the mobile teams reported high turn-over among participants; after the fifth cycle of the intervention, more than half of FSW were identified as first time participants (23). This is supported by consistent associations between increased health screening behaviors and reported exposure to the intervention.…”
Section: Discussionmentioning
confidence: 99%